Can False Memories Prime Problem Solutions for Healthy Older Adults and Those With Alzheimer's Disease?. (5th June 2018) - Akhtar, Shazia; Howe, Mark L; Hoepstine, Kedron
Abstract: Objective: Recent research has shown that false memories can have a positive consequence on human cognition in both children and young adults. The present experiment investigated whether false memories could have similar positive effects by priming solutions to insight-based problems in healthy older adults and people with Alzheimer's disease (AD). Method: Participants were asked to solve compound remote associate task (CRAT) problems, half of which had been preceded by the presentation of Deese/Roediger-McDermott (DRM) lists whose critical lures (CL) were also the solutions to those problems. Results: The results showed that regardless of cognitive ability, when the CL was falsely recognized, CRAT problems were solved more often and reliably faster than problems that were not primed by a DRM list. When the CL was not falsely recognized, CRAT problem solution rates and times were no different from when there was no DRM priming. Discussion: These findings are consistent with predictions from theories of associative activation and demonstrate the importance of automatic spreading activation processes in memory across the life span.